2016
DOI: 10.1038/hdy.2016.43
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and estimation of effective population size

Abstract: Effective population size (N e ) is a key parameter in population genetics. It has important applications in evolutionary biology, conservation genetics and plant and animal breeding, because it measures the rates of genetic drift and inbreeding and affects the efficacy of systematic evolutionary forces, such as mutation, selection and migration. We review the developments in predictive equations and estimation methodologies of effective size. In the prediction part, we focus on the equations for populations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
343
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(346 citation statements)
references
References 181 publications
2
343
0
1
Order By: Relevance
“…In contrast, NeEstimator V2 (Do et al 2014) does not assume that all samples are from a single cohort, and has been previously used to estimate N e in bats (Plecotus auritus; Razgour et al 2014). We, therefore, chose this method as the most appropriate for our data set, recognizing that methods for estimating N e each have their own strengths and weaknesses (Wang et al 2016;Waples 2016). …”
Section: Microsatellite Analysismentioning
confidence: 99%
“…In contrast, NeEstimator V2 (Do et al 2014) does not assume that all samples are from a single cohort, and has been previously used to estimate N e in bats (Plecotus auritus; Razgour et al 2014). We, therefore, chose this method as the most appropriate for our data set, recognizing that methods for estimating N e each have their own strengths and weaknesses (Wang et al 2016;Waples 2016). …”
Section: Microsatellite Analysismentioning
confidence: 99%
“…The mitochondrial DNA study by Klütsch et al (2012) found that while both Manitoba and Ontario animals expanded from (Wang, Santiago, & Caballero, 2016). The mitochondrial DNA study by Klütsch et al (2012) found that while both Manitoba and Ontario animals expanded from (Wang, Santiago, & Caballero, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although estimates of genetic diversity were mostly high and fairly uniform, temporal analyses of changes in N e show that contemporary populations have dramatically reduced effective population sizes compared to historic levels. Because N e accuracy is affected by sample size, marker numbers, and marker polymorphism Waples et al, 2014;Wang et al, 2016), performing cohort analysis, increasing the numbers of polymorphic molecular markers, sample size, and spatial coverage throughout the archipelago would allow for enhanced assessments of the genetic population dynamics of Nassau grouper. The application of more sophisticated molecular techniques than microsatellites, for example, RAD-sequencing, which can identify thousands of single nucleotide polymorphisms (SNPs), could help to resolve potential fine-scale intraspecific genetic structure (e.g., Larson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%